2001
DOI: 10.1046/j.1365-2362.2001.00892.x
|View full text |Cite
|
Sign up to set email alerts
|

Reassignment of the EPB4·1 gene to 1p36 and assessment of its involvement in neuroblastomas

Abstract: Out of 72 neuroblastomas we have identified 11 tumours with impaired EPB4.1 expression and 5 tumours with significant sequence changes. We also found that the 135 kDa isoform is the main EPB4.1 product in neuroblastoma. EPB4.1 cDNA from a neuroblastoma cell line produced a 135-kDa protein and displayed a cytoplasm/membrane localization in transfected cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…To further demonstrate the specificity of dematin-GLUT1 interaction, we transfected an Xpress-tagged protein 4.1R construct and GLUT1 in HEK293T cells. We have previously shown that this 4.1R construct expresses both 80-and 135-kDa isoforms of protein 4.1R (23). Co-immunoprecipitation of protein 4.1 using an Xpress monoclonal, under the same conditions as used for the dematin-GLUT1 interaction, did not immunoprecipitate GLUT1 (Fig.…”
Section: Resultsmentioning
confidence: 76%
“…To further demonstrate the specificity of dematin-GLUT1 interaction, we transfected an Xpress-tagged protein 4.1R construct and GLUT1 in HEK293T cells. We have previously shown that this 4.1R construct expresses both 80-and 135-kDa isoforms of protein 4.1R (23). Co-immunoprecipitation of protein 4.1 using an Xpress monoclonal, under the same conditions as used for the dematin-GLUT1 interaction, did not immunoprecipitate GLUT1 (Fig.…”
Section: Resultsmentioning
confidence: 76%
“…However, these studies have not identified a consistent region of deletion. Furthermore, these and other studies have proposed over 20 genes within these regions as candidate neuroblastoma tumor suppressors, none of which have yet been proven to play a significant causative role in neuroblastoma tumor development (Ejeskar et al, 2000;Judson et al, 2000;De Toledo et al, 2001;Huang et al, 2001;Abel et al, 2002;Cerignoli et al, 2002;Krona et al, 2003;Thompson et al, 2003;Mathysen et al, 2004). Our current work was designed to determine the location and extent of 1p deletion in a very large primary tumor cohort by extensive genotyping, sequencing, gene identification, and transcript characterization.…”
Section: Discussionmentioning
confidence: 98%
“…In this regard, Protein 4.1R and Protein 4.1B have been reported to function as negative growth regulators in the pathogenesis of a diverse number of human cancers (Tran et al, 1999;Huang et al, 2001;Charboneau et al, 2002), including meningiomas (Gutmann et al, 1997Perry et al, 2000;Robb et al, 2003). The present study was undertaken to define the critical domain of Protein 4.1B necessary for meningioma growth suppression as a first step towards elucidating the molecular mechanism underlying Protein 4.1B function.…”
Section: Discussionmentioning
confidence: 99%